Coordination polymer-derived nano-sized zinc ferrite with excellent performance in nitro-explosive detection. Issue 34 (15th August 2017) - Singha, Debal Kanti; Mahata, Partha
Abstract : Synthesis of nano-sized zinc ferrite using coordination polymer as a single source precursor through thermal decomposition is reported and its luminescence based selective detections have been achieved for the phenolic nitroaromatics. Abstract : Herein, a mixed metal coordination polymer, {(H2 pip)[Zn1/3 Fe2/3 (pydc-2, 5)2 (H2 O)]·2H2 O}1 {where H2 pip = piperazinediium and pydc-2, 5 = pyridine-2, 5-dicarboxylate}, was successfully synthesized using a hydrothermal technique. To confirm the structure and phase purity of1, single crystals of an isomorphous pure Fe compound, {(H2 pip)[Fe(pydc-2, 5)2 (H2 O)]·2H2 O}1a, were synthesized based on similar synthetic conditions. Single crystal X-ray data of1a confirmed the one-dimensional anionic metal–organic coordination polymer hydrogen bonded with protonated piprazine (piperazinediium) and lattice water molecules. The phase purity of1 and1a were confirmed via powder X-ray diffraction. Compound1 was systematically characterized using IR, TGA, SEM, and EDX elemental mapping analysis. Compound1 was used as a single source precursor for the preparation of nano-sized ZnFe2 O4 via thermal decomposition. The as-obtained ZnFe2 O4 was fully characterized using PXRD, SEM, TEM, and EDX elemental mapping analysis. It was found that ZnFe2 O4 was formed in its pure form with particle size in the nano-dimension. The aqueous dispersion of nano-sized ZnFe2 O4 exhibits a strong emission at 402 nm upon excitation at 310 nm. This emissive property was employed for luminescence-based detection of nitroaromatic explosives in an aqueous medium through luminescence quenching for the first time. Importantly, selective detections have been observed for phenolic nitroaromatics based on differential luminescence quenching behaviour along with a detection limit of 57 ppb for 2, 4, 6-trinitrophenol (TNP) in water.